The Effect of Problem Based Learning Assisted by Spin Happy Media on Students' Conceptual Understanding - Ayu Setiawati, Tria; Yunitiara Rizqi, Hesti (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
This study aims to examine the effect of Problem-Based Learning (PBL) assisted by Spin Happy media on students' conceptual understanding. The research employed a quasi-experimental design with a pretest-posttest control group. The population consisted of elementary school students, with samples selected using purposive sampling. Data were collected through a conceptual understanding test and analyzed using an independent sample t-test and simple linear regression. The results indicated that students in the class implementing Problem-Based Learning Assisted by Spin Happy achieved significantly higher conceptual understanding scores compared to those in the conventional learning class, with the experimental group's mean score (89.77%) being higher than the control group's mean score (74.40%). This study suggests that integrating Problem-Based Learning with interactive media such as Spin Happy can enhance student engagement and conceptual understanding in learning.